Methodology for implementation of autonomous photogrammetric missions with fixed-wing UAS platforms - Ferencz-Appel, Amit (2021)
In this work, a methodology developed to execute autonomous photogrammetric missions with fixed-wing unmanned aerial systems is proposed, based on the open-source software and hardware project Paparazzi UAV [1]. The methodology consists of four main stages: mission planning, system conditioning, mission execution, and data processing. The methodology was validated through the planning of photogrammetric missions and their execution with the Opterra 2M [2] platform and the Apogee controller [3].